PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN "IMAKO" SISWA KELAS VII SMP NEGERI 1 TUGU TRENGGALEK (Education Journal : Journal Educational Research and Development, 2017)
One of the most student difficulty in the science learning in Basic Competency Biological Classification is the ability to remember very diverse classification of species. Student difficult to get the real visualisation of biodiversity as learning resource. Therefore it is need for additional media to represent the diversity of living things that not found in the student learning environment. One of the learning models is IMAKO ( Identification and Enter into the Identity Box). Classroom Action Research carried out at VII H Class in Junior High School I Tugu school year 2013-2314. The research flow is early reflection, planning, action, observation, reflection, adn redesign. CAR is designed in two cycles for 4 meetings and consist of the planning stage, action, observing, and reflecting. The result of the research is the applicatin of IMAKO learning model can improve the student’s learning result, the liveliness and motivation of the student by 12%, the increase of Competency Test value from cycle 1 to cycle 2 is 18 %.